Efficacy of cognitive behavioural therapy for clients who have sustained a traumatic brain injury (TBI) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Psychology at Massey University, Wellington, New Zealand - Christianson, Muriel Katherine (Massey University, 2009)
While the focus of rehabilitation following traumatic brain injury (TBI) is often on management of physical and cognitive impairments, emotional and behavioural changes in the person with the injury may represent major hurdles in adjustment following injury. Mood, anxiety and adjustment disorders are common following TBI. A manualised cognitive behavioural therapy (CBT) treatment programme was developed that incorporated provision of education on consequences of TBI, used cognitive and behavioural strategies to recognise and manage emotional reactions to injury, and promoted achievement of personal goals. Participants were nine people with TBI referred to Massey University Psychology Clinic Wellington, for psychotherapy to assist in managing symptoms of psychological distress or adjustment difficulties following injury. Measures used included the Hospital Anxiety and Depression Scale (HADS) to monitor progress in reduction of symptoms of Anxiety and Depression; the Patient Competency Rating Scale (PCRS) to assess competency across areas of day-to-day living; and the Homework Rating Scale Second Edition (HRS-II) to assess the value of homework assignments for participants. Results were presented graphically in group format and in the form of individual case studies outlining progress in achieving individual goals. There was considerable variation in the responses of participants to treatment. When anxiety and depression were secondary to other referral issues such as fatigue and pain that remained high over treatment sessions, there was limited movement on HADS Anxiety and Depression scores. The small number of participants impacted on the ability to detect differences between Patient and Informant ratings on the PCRS or to demonstrate increased levels of awareness over treatment sessions. Consistent completion of Homework assignments proved difficult for participants. Factors that impacted on achievement of personal goals included ongoing levels of fatigue and pain, levels of personal expectation, interpersonal and organisational skills, insight into emotional reactions, and good family and social support. There is a part for a CBT approach in adjusting to changes following TBI, particularly in assisting with reassessing expectations following injury.
Keywords: Cognitive Behaviour Therapy; CBT; Brain damage patients; Traumatic brain injury; TBI; Rehabilitation; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology